PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT MOKA TEKNOLOGI INDONESIA - Shania Zuliana Harahap; Cahyo Pramono; Hasrul Azwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study aims to determine the effect of reward and punishment on the employee performance of PT Moka Teknologi Indonesia. In this study uses a quantitative approach, with sample of 25 respondents. The data analysis technique use is multiple regression analysis which serves to prove the research hypothesis. Based on results, the t count value of the reward variable is 0,251, it can be concluded that the reward has not significant effect on the performance of employee of PT Moka Teknologi Indonesia. The t count value of the punishment variable is 0,018, it can be concluded the punishment variable has a positive and significant effect on the performance of employee PT Moka Teknologi Indonesia. Reward and punishment simultaneously has a positive effect on performance of employee of PT Moka Teknologi Indonesia. The results R square is 70,7%, which means that the reward and punishment variable has an effect on performance of employee variable. While the remaining 29,3% has an effect by other variable not in this study. Keywords: punishment, reward, employee performance